Measuring regional resilience towards fossil fuel supply constraints. Adaptability and vulnerability in socio-ecological Transformations-the case of Austria. (April 2016) - Exner, Andreas; Politti, Emilio; Schriefl, Ernst; Erker, Susanna; Stangl, Rosemarie; Baud, Sacha; Warmuth, Hannes; Matzenberger, Julian; Kranzl, Lukas; Paulesich, Reinhard; Windhaber, Markus; Supper, Susanne; et al.
Abstract: Resilience has become a prominent concept to understand system vulnerabilities and flexible ways of adapting to crises. Recently, it gained importance in discussions about the possible peak in oil production (peak oil) and its consequences, which might affect economic performance, social well-being and political stability, and thus also the energy transition to a low-carbon economy. The paper presents a new way of measuring resilience as absolute resilience related to a best practice-model of a resilient society. The resilience model is grounded in explicit theoretical assumptions. All indicators are justified by theoretical and empirical arguments. We present a case study of Austrian municipalities and broader-scale spatial types, which were defined according to their degree of urbanization. The mean resilience of Austrian municipalities is moderate, the difference between resilience values of municipalities is small. Significant differences between spatial types exist. Higher resilience is displayed by less urbanized types due to a higher share of agricultural activities and a more favorable level of GDP per capita. Austria has considerable latitude to improve resilience. Corresponding policies should target resilience components with the lowest values first. A sole focus on regionalization is not recommended. These conclusions are applicable to OECD countries in general. Highlights: Mean resilience of Austrian municipalities towards peak oil is moderate. The difference between resilience values of municipalities is small. Significant differences in resilience between spatial types exist. Higher resilience is displayed by less urbanized types. Policies should target resilience components with the lowest values first.